Argumentasi Pengajuan Kasasi Oleh Penuntut Umum Terhadap Putusan Judex Factie Dalam Perkara Penggelapan Dalam Jabatan - Zulmi Tafrichan (Sebelas Maret University, 2017)
The purpose of this research are about compatibility of prosecutor’s argumentation who submit the cassation with article 253 on Criminal Code Procedures about judex factie verdict which is release the defendant from every lawsuits and a question abaut did the judex juris argumentation is compatible with Article 256 jo. Article 193 act (1) on Criminal Code Procedure. This normative law researchis aprescriptive research with using case approach method. This research is relative to one of cassation submission on in Pematangsiantar which is conducted by Nicko Fernando Simanjuntak. In 14th August 2014 Pematangsiantar District Court imposed verdict number:74/ Pid.B/2014/PN.PMS which is said that Nicko Fernando Simanjuntak is prooved doing an action which is verdicted by Prosecutor, but that action is not a crime then he Judge verdictedto release the defendant from every demand. From Pematangsiantar District Court’s verdict number:74/ Pid.B/2014/PN.PMS Prosecutor is applying a cassation request with a reason that the verdict is not applied as it should be. The results of this research show that the Prosecutor’s cassation request is fulfill the formal terms according article 244 until article 248 on Criminal Code Procedure which basically set to the decision of the criminal case on the last level, Prosecutor may submit to the Supreme Court of Cassation examination unless to the free verdict so acceptable to be examined and decided upon the Supreme Court, beside that it also qualify the material term in accordance with Article 253 paragraph (1) letter a Criminal Code which is basically to determine whether a rule of law is not applied or applied is not as it should be, then about the argument of Judex Juris in granting cassation Attorney / General Prosecutor in a on fraud of occupation case of the Supreme Court's decision No. 99 K / PID / 2015 had been is compatible with Article 255 paragraph (1) jo. with Article 256 on Criminal Code Procedure in addition to the arguments Judex Juris in granting cassation in the State Prosecutor of Pematangsiantar also compatible with the provisions of Article 256 jo. with Article 193 paragraph (1) Criminal Procedure CodeKeywords: Cassation, Prosecutor And Fraud of Occupation Case